Structures for strategy : institutional preconditions for long-range planning in cross-country perspective - Zorn, Justin (2012)
From climate change to economic instability, a range of persistent interdisciplinary challenges has heightened calls for a more integrative approach to policy planning in the US federal government. Long-range planning processes are still largely compartmentalized within executive branch departments. While much of the literature on US planning attributes the absence of systematic coordination in long-term policy planning to several characteristics inherent in modern representative governments including frequent electoral turnover, bureaucratic competition for influence, pervasive media leaks, and difficulty accruing political gains from crisis prevention, such analyses fail to account for why other representative governments including the United Kingdom have established more centralized strategic planning architecture. The UK Government created a National Foresight Programme in 1994 to track multidisciplinary long-range issues related to innovation and a Horizon Scanning Centre in 2004 to coordinate priority-setting, risk assessment, and strategy formation across a range of departmental jurisdictions. Drawing on interviews with government officials and analysis of organizational arrangements, speeches, and memoranda, this paper seeks to investigate why the US federal government maintains a compartmentalized framework for strategic planning while the UK has adopted a more centrally-coordinated framework. By briefly comparing a series of secondary case studies including Brazil, India, South Korea, and Singapore, the paper seeks to identify a more general set of institutional preconditions for the development of interdisciplinary planning programs at the national level.